PENERAPAN AKUNTABILITAS ANGGARAN UNTUK PENGUKURAN EFISIENSI DAN EFEKTIVITAS RENCANA ANGGARAN BIAYA (Studi Kasus pada PT. PELINDO Kantor Cabang Pulau Baii Bengkulu) - -, Asa'd (JURNAL EKOMBIS REVIEW, 2014)
Asa?d; PT Pelindo constitute of BUMN that have a range in sea transportation field. As well as the other company in Indonesia that have a range in transportation, the rise of BBM price can make an impact for PT Pelindo, which caused BBM price component rise until 46,12% from the price total of shipping. Therefore, company try to increase the effeciency in every each of aspect, also increasing internal supervision to manage cost side with tight. Accountability application can encourage the company to achieve the purpose through cost control. Based from the background, the purpose of this observation is make a research about accountability application in reach of cost control. This observation use qualitative approach. This observation also literature and interview with financial staff from PT Pelindo Pulau Baii Branch Office Bengkulu to get the Data. The analysis method from the observation is comparing accountability application and cost control that obtainable from case study. Based on the result of PT Pelindo Pulau Baii Branch office Bengkulu, the company not yet to apply a good accountability, it is knew from presence some requirements and characterization which not yet to filled. The company also not yet to run the cost control in good way, this can see from the analysis presence against of cost digression which not implemented. Budget management in PT Pelindo Pulai Baii Branch office Bengkulu is adequate in effective and efficient. Key words: Accountability Budget, Effectiveness and Effeciency.